School level resources and students’ performance in Malaysian national type Chinese schools - Kenayathulla, Husaina Banu; Ling, Hee Fui; Razak, Ahmad Zabidi Abdul; Darusalam, Ghazali (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2019)
The Malaysian government has always prioritised investment in education by providing quality education as one of the aspirations envisioned in the Malaysian Education Blueprint. Quality education is often associated with better learning environment, adequate resources, and quality teachers. Previous studies in Malaysia were mainly focused on socio-economic factors that determine students’ performance and were consistently focused on students’ performance in national schools. This study aims to identify school level factors that determine National Type Chinese School students’ performance in UPSR examinations. This study also analyses whether there are gaps in school level resources between higher performing and lower performing Chinese schools. Questionnaires were distributed to two hundred teachers in National Type Chinese schools around the area of Kuala Lumpur and Selangor, Malaysia. Data were then analysed using inferential statistics such as multiple regression analysis and t-test. Results indicate that band of school, number of teachers, small class size, average parents’ income, fund allocated, instructional materials, science laboratory, teacher shortage and leadership are important school level factors that determine students’ performance in UPSR examinations. The findings show that teachers perceive that there are significant differences between higher performing and lower performing schools in terms of school resources such as books, internet connections, teachers’ leadership, classroom management. These findings provide insights to policy makers on the necessary policy interventions that need to be taken to ensure quality education regardless of the performance of schools. © 2019, University of Malaya. All rights reserved.